ANALISIS MOTIVASI KERJA PEGAWAI KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH KOTA JAMBI - Juliansyah, Dedi Ferry; Ardinal, Ardinal; Sumarni, Sumarni (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
Development.Â Planning Board of Jambi City. This study aims to determine how the work motivation of the Regional Development Planning Agency of Jambi City in terms of intrinsic and extrinsic motivation. The research methodology used in this research is a descriptive analysis using data collection method through questionnaire, documentation, literature study. Respondents in this research are employees of the Regional Development Planning Board of Jambi City. The results of this study indicate that the overall motivation of employees of the Development Planning Agency of Jambi City has been running quite well. The situation is indicated by the percentage of motivation factors that get the response from the employees. From this research, it can be concluded that the employees of the Regional Development Planning Agency of Jambi City are motivated to perform the tasks, although there are several obstacles. Based on this research, it can be mentioned several suggestions to the Development Planning Board of Jambi City to maintain and improve the motivation of their existing employees, enhance the system of Corporate Administration Policy and Supervision to the employees so that they can understand and perform their duties well.